Duration of ADHD medication treatment among Finnish children and adolescents - a nationwide register study - Kolari, Terhi A.; Vuori, Miika; Rättö, Hanna; Varimo, Eveliina A.; Aronen, Eeva T.; Auranen, Kari; Saastamoinen, Leena K.; Ruokoniemi, Päivi T. (SPRINGER, 2025)
Aim: To study the duration of attention-deficit/hyperactivity disorder (ADHD) medication treatment among children and adolescents by sex and age group in Finland during 2008-2019.
Methods: This was a descriptive, population-based register study covering all Finnish children and adolescents aged 6-18 years who initiated their first ADHD medication treatment period between January 1, 2008 and December 31, 2019 (n = 40691). To establish the duration of use we collected data from the register of Dispensations reimbursable under the National Health Insurance Scheme register. The median follow-up time was 3.8 years (Q1 = 1.7, Q3 = 7.1). Treatment duration was calculated as the interval between the date of the first and last purchase with a cut-off of 365 days allowed between purchases. The durations were estimated using Kaplan-Meier survival times.
Results: The median duration of ADHD medication treatment was 3.2 years (95% CI 3.2, 3.3, Q1 = 1.0 95% CI 0.9, 1.0, Q3 = 6.8 95% CI 6.7, 7.0). Sex and age significantly influenced treatment duration (p <.0001 and p <.0001). Boys had longer treatment duration than girls and the younger the subject, the longer the duration of usage. Boys aged 6-8 years (32.4% of the subjects) exhibited the longest treatment duration with a median of 6.3 years (95% CI 6.2, 6.5, Q1 = 2.6 95% CI 2.5, 2.7, Q3 = 9.4 years 95% CI 9.2, 9.6).
Conclusions: The duration of ADHD medication treatment among children in the real-world clinical setting goes well beyond the data available from randomized controlled trials and extends for several years especially among young boys.